El recurso didáctico del internet en la enseñanza aprendizaje en el área de ciencias naturales, bloque tres en los niños y niñas del séptimo grado del subnivel básico medio del centro educativo general básico “Fernando Chávez” del barrio Chinguilanchi, parroquia El Valle, cantón y provincia de Loja, período lectivo 2013-2014 - Minga Diaz, Oswaldo Enrique (2016)
The investigative work The resource Teaching "Internet in the teaching learning in the AREA of science natural, block three in the boys and girls of the 7th grade of the basic SUBLEVEL of the central educational GENERAL basic FERNANDO CHAVEZ" of the CHINGUILANCHI district, parish Valley, CANTON and province of LOJA period school year 2013-2014; whose general objective to was contribute to an essential improvement in the use of Internet as a teaching resource in the Teaching Learning Process in the Area of Natural Sciences of children Seventh Grade of Basic Sublevel Middle Education Center General Basic "Fernando Chávez”; the research design was cross; the methods used were the scientist, inductive, deductive, descriptive; technique of the survey and their instrument was the questionnaire, results showed that the investigated educational center has few technological resources for the learning of their students; the population was 2 teachers and twenty-eight students, concluding that they should seek support from the authorities, with the aim of achieving necessary technological implements to ensure that the quality and diversity of learning experiences in the classroom are significant.